Exploring the concept of Islamization of knowledge from scholarly perspectives - Samsuri, Maimanah; Tengku Paris, Tengku Nazatul Shima; Mazlan, Siti Aisyah; Mohd Ismath, Nurul Hanilah; Kembaren, Mardiah Mawar; Kembaren, Farida Repelita Waty Br (e-International Publishing House, U.K., 2024)
53Exploring the Concept of Islamization of Knowledge from Scholarly Perspectives Maimanah Samsuri1, Tengku Nazatul Shima Tengku Paris2, Siti Aisyah Mazlan3, Nurul Hanilah Mohd Ismath4,Mardiah Mawar Kembaren5, Farida Repelita Waty Br Kembaren61Academy of Language Studies, Universiti Teknologi MARA, Cawangan Pahang, Kampus Raub, Raub, Malaysia, 2 Academy of Language Studies, Universiti Teknologi MARA, Cawangan Pahang, Kampus Raub, Raub, Malaysia, 3Academy of Language Studies, Universiti Teknologi MARA, Cawangan Pahang, Kampus Raub, Raub, Malaysia, 4 International Islamic University Malaysia, Pagoh Branch, Pagoh, Malaysia, 5Universitas Sumatera Utara, Kota Medan, Sumatera Utara, Indonesia, 6Fakultas Ilmu Tarbiyah dan keguruan,Universitas Islam Negeri Sumatera Utara, Sumatera Utara, Indonesiamaimanah@uitm.edu.my, tnshima@uitm.edu.my, sitiaisyah370@uitm.edu.my, hanilah@iium.edu.my,mardiah@usu.ac.id. faridarepelita@uinsu.ac.idTel : +609-3515439AbstractThe study investigates the process of Islamization of Knowledge by conducting a bibliometric analysis of documents published in the Scopus database between 2010 and 2024. The findings demonstrate a favourable yearly pattern of publications and emphasise Malaysia's prominent position in this domain, with notable contributions from two well-known universities. The study also shows Muslim thinkers' diverse vocabulary and conceptual methodologies. This analysis serves as a helpful point of reference for future studies. It contributes to a deeper comprehension of the process of Islamization of Knowledge by identifying areas where further research is needed